Polyetheretherketone custom-made implants for craniofacial defects: Report of 14 cases and review of the literature. Issue 7 (September 2015) - Alonso-Rodriguez, E.; Cebrián, J.L.; Nieto, M.J.; Del Castillo, J.L.; Hernández-Godoy, J.; Burgueño, M.
Abstract Background Craniofacial defects tend to carry functional and esthetic consequences for the patient. The complex shapes in this region make such reconstructions a challenging procedure and the most suitable material to be used remains controversial. Methods We report a series of 14 patients whose craniofacial defects were reconstructed using a computer designed PEEK-PSI (Polyetheretherketone- Patient Specific Implant). We analyzed the complications and outcomes of PEEK custom-made implants and compared our results with those of other case series reported in the current literature. Results Fourteen patients underwent craniofacial reconstruction using a PEEK-PSI. Three cases involved a one-step primary reconstruction and the rest of cases underwent a delayed reconstruction. Two cases (14.3 %) presented infection and only in one case was the implant definitively removed. Esthetic results were considered to be highly satisfactory. Conclusion With CAD-CAM techniques, it is possible to prefabricate an individual implant. The ideal material for reconstructing maxillofacial defects does not exist, but PEEK has demonstrated good outcomes. When autologous bone is not available or, in selected cases with large or complex defects in the maxillofacial area, PEEK is one of the best options to reconstruct these defects. However, further studies are needed to determine the long-term results.